A STUDY ON AWARNESS AND SATISFACTION OF BENEFICIARY TOWARDS ESI SCHEME IN THOOTHUKUDI DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
The Employees State Insurance Scheme is an integrated measure of social insurance embodied in the Employees State Insurance Act and it is designed to accomplish the task of protecting employees as defined in the Employees State Insurance Act, 1948 against the impact of incidences of sickness, maternity, disablement and death due to employment injury and to provide medical care to insured person and their facilities. The aim of the study is to study the demographic profile of the respondents, to understand the awareness of ESI schemes and to identify whether the insured persons are satisfied with the services provided by ESI. The study was based on primary data were collected from the respondents directly with the help of questionnaire. Secondary data were collected from books, journals and websites. 150 respondents from the Thoothukudi district were selected at simple random sampling method. The collected data were analyzed with the help of Chi – Square Test. Chi – Square is used to find out relationship between demographic profile and their level of satisfaction of the respondents towards services of ESI. The present study is an attempt to assess the awareness and satisfaction of beneficiary towards Employee State Insurance Scheme.